Effects of Mulching and Plant Spacing on Growth, Yield and Quality of Watermelon (Citrullus Lanatus) in Rapti Riverbed, Dang, Nepal - Neupane, R; Tripathi, KM; Panthi, Bhawana; Sapkota, Poonam (SAARC Journal of Agriculture, 2023)
A field experiment was conducted at Rapti riverbed, Dang, Nepal to study the effects of mulching and plant spacing on growth, yield, and fruit quality of Mastana- a hybrid cultivar of watermelon- during February-May 2019. The two-factor experiment had three types of mulching- black silver polythene, rice straw, and control (no mulch), and three different plants spacing- 2m×1m, 2m×1.5m, and 2m×2m. The experiment was laid out in randomized complete block design with three replications. The result showed both mulching and plant spacing significantly influence growth, yield and quality of watermelon. Considering the mulching materials, the minimum days required for germination (14.44 days), the longest main vine length (316 cm), maximum number of leaves per plant (99.42), the highest individual fruit weight (7.30 kg) and fruit yield mt ha-1 (122.1), the maximum TSS and vitamin C content (12.11°B and 18.76 mg/100 g) were recorded from the plants grown under black silver polythene mulch and the lowest values were recorded from the plants grown without mulching except days required to germination and titratable acidity. In case of plant spacing, the higher yield was recorded in 2m×1m plant spacing (140.3 mt ha-1) as compared to 2m×1.5m (95.5 mt ha-1) and 2m×2m (75.2 mt ha-1). Likewise, effect of plant spacing on the number of leaves plant-1 was significant in 40 DAS, and 80 DAS. Therefore, Mastana, a hybrid cultivar of watermelon is recommended to grow on black silver polythene with 2m×1m plant spacing in Rapti Riverbed conditions. SAARC J. Agric., 21(2): 41-52 (2023)